Changes in Utilization and Discard of Hepatitis C–Infected Donor Livers in the Recent Era. Issue 2 (24th August 2016) - Bowring, M. G.; Kucirka, L. M.; Massie, A. B.; Luo, X.; Cameron, A.; Sulkowski, M.; Rakestraw, K.; Gurakar, A.; Kuo, I.; Segev, D. L.; Durand, C. M.
Abstract : The impact of interferon (IFN)‐free direct‐acting antiviral (DAA) hepatitis C virus (HCV) treatments on utilization and outcomes associated with HCV‐positive deceased donor liver transplantation (DDLT) is largely unknown. Using the Scientific Registry of Transplant Recipients, we identified 25 566 HCV‐positive DDLT recipients from 2005 to 2015 and compared practices according to the introduction of DAA therapies using modified Poisson regression. The proportion of HCV‐positive recipients who received HCV‐positive livers increased from 6.9% in 2010 to 16.9% in 2015. HCV‐positive recipients were 61% more likely to receive an HCV‐positive liver after 2010 (early DAA/IFN era) (aRR:1.45 1.611.79, p < 0.001) and almost three times more likely to receive one after 2013 (IFN‐free DAA era) (aRR:2.58 2.853.16, p < 0.001). Compared to HCV‐negative livers, HCV‐positive livers were 3 times more likely to be discarded from 2005 to 2010 (aRR:2.69 2.993.34, p < 0.001), 2.2 times more likely after 2010 (aRR:1.80 2.162.58, p < 0.001) and 1.7 times more likely after 2013 (aRR:1.37 1.682.04, p < 0.001). Donor HCV status was not associated with increased risk of all‐cause graft loss (p = 0.1), and this did not change over time (p = 0.8). Use of HCV‐positive livers has increased dramatically, coinciding with the advent of DAAs. However, the discard rate remains nearly double that of HCV‐negative livers. Further optimization of HCV‐positive liver utilization is necessary to improve access for all candidates. Abstract : In this registry‐based study, the authors report that in the era of highly effective antiviral therapies for hepatitis C (HCV), use of HCV+ donor livers has increased, outcomes after HCV+ transplantation are comparable to HCV– transplantation, and yet discard rates of HCV+ livers remain elevated.